Bureaucratic influence in the formulation of public policy: the case of the system of high public management in Chile - Araya, Juan Pablo (Política. Revista de Ciencia Política, 2016)
How bureaucrats influence in policy formulation? The mainstream of literature postulates that the policy formulation is led by politicians who define the scope of these. However, alternative approaches argue that bureaucrats influencein this process. The aim of this study is to analyze the mechanisms whereby bureaucrats influence policy formulation, through the case study of Sistema de Alta Dirección Pública en Chile (SADP). Evidence indicates that bureaucrats influence on those policies that politicians are not interested, leaving wideareas of discretion, and for a specific expertise that differentiates them from other actors as technocrats or technopols.